Do estigma social à invisibilidade : a pessoa com deficiência física nas políticas públicas voltadas para a redução de desastres - Geraldi, Débora (2016)
In contact with some specific agents, the disordered occupation of the cities reveals risks that were somewhat dormant. Rain can be considered one of these agents, because your interaction with the environment often affects the routines of places, promoting various disruptions to the lives of people, including a disaster situation. The Civil Defense is the agency responsible for the security of the population in these events and considers in their manuals that some groups are more vulnerable: people with physical disabilities are one of this. Thus, the objective was to analyze sociologically how a person with disabilities is considered by the Civil Defense and by the scientific literature in the context of disaster, seeing there is a gap in sociological literature as concerning the analysis of disabled people and their interaction with the biophysical environment. To this end, we conducted a survey to review documents and protocols provided by the Brazilian Civil Defense, as well as documents and studies available in online research platforms, which analyze the interaction of disability with disasters, and thereby discriminating the foci predominant theme in contemporary studies. The aim is to present a synthesis of sociological knowledge about the group in the context of disasters.